Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada MPS KUD Tani Bahagia - Nafakhati Salma Nuha; Mohammad Khusnu Milad (Jurnal Ilmiah Ekonomika & Sains, 2025)
This study aims to analyze the influence of compensation and work motivation on employee performance at MPS KUD Tani Bahagia Mojokerto. The research employed a quantitative approach with a population of 47 employees and a sample of 32 respondents selected through a cluster random sampling technique. Data were collected using a five-point Likert scale questionnaire and analyzed through validity tests, reliability tests, multiple linear regression, F-test, and t-test using SPSS 25. The results show that compensation has a positive and significant effect on employee performance (sig. 0.000 < 0.05; coefficient 0.722), while work motivation also has a positive and significant effect (sig. 0.000 < 0.05; coefficient 0.418). Simultaneously, compensation and work motivation significantly affect employee performance (F = 62.669; sig. 0.000 < 0.05). The R Square value of 0.812 indicates that 81.2% of employee performance variation is influenced by these variables, while 18.8% is explained by other factors. The findings highlight that fair compensation and high work motivation significantly contribute to improved employee performance.